The effects of surface functionality and size of gold nanoparticles on neuronal toxicity, apoptosis, ROS production and cellular/suborgan biodistribution - Özçiçek, İlyas; Ayşit, Neşe; Çakıcı, Çağrı; Aydeğer, Asel (Elsevier B.V., 2021)
Gold nanoparticles are emerging as promising nanomaterials to create nanoscale therapeutic delivery systems. The aim of the study was to synthesis of highly monodisperse and stable gold nanoparticles functionalized with polyethyleneimine (PEI) and polyethylene glycol (PEG), multiparametric investigation of their neuronal toxi-cological effects and evaluation of the cellular/suborgan biodistribution. Gold nanoparticles (AuNP20 and AuNP50) were synthesized and their surfaces were electrostatically modified by PEI and PEG. Dorsal root gan-glion (DRG) sensory neurones were isolated from BALB/c mice. Cell viability, apoptosis and ROS production were evaluated in vitro. Cellular and suborgan biodisribution of the AuNPs were investigated using inductively coupled plasma mass spectrometry (ICP-MS) technique. PEI and PEG surface coating increased both biocom-patibility and biodistribution of the AuNPs. ICP-MS measurements showed the presence of gold in liver, spleen, kidney, heart, blood and brain within a 30 days period. The size and surface chemistry of the AuNPs are important parameters for potential nanoteranostic applications in the future studies.
Keywords: Biodistribution; DRG Sensory Neuron; Gold Nanoparticle; Nanotoxicity; PEI/PEG Surface Functionalization